Impact of satisfaction with physician-patient communication on self-care and adherence in patients with hypertension: cross-sectional study - Natalia Świątoniowska-Lonc; Jacek Polański; Wojciech Tański; Beata Jankowska-Polańska (BMC, 2020)
Abstract Background Hypertension (HT) requires patients to continuously monitor their blood pressure, strictly adhere to therapeutic recommendations, and self-manage their illness. A few studies indicate that physician-patient communication and the patient's satisfaction with the therapeutic relationship may affect the course and outcomes of the treatment process. Research is still lacking on the association between satisfaction with physician-patient communication and adherence to treatment or self-care in chronically ill patients. The aim of the study was to evaluate the relationship between satisfaction with physician-patient communication and self-care and adherence in patients with HT undergoing chronic treatment. Methods The following instruments were used: the Adherence to Refills and Medication Scale (ARMS) for evaluating adherence (12-48 points), the Self-Care of Hypertension Inventory (SCHI) for self-care level (0-100 points), and the Communication Assessment Tool (CAT) for evaluating satisfaction with physician-patient communication. Socio-demographic and clinical data were obtained from patients' medical records. The research has a cross-sectional and observational study design. Inclusion criteria were as follows: age > 18 years, hypertension diagnosed per European Society of Hypertension (ESH) guidelines, treatment with at least one antihypertensive drug for the past 6 months, and informed consent. Cognitively impaired patients unable to complete the surveys without assistance were excluded (MMSE ≤18). Correlations between quantitative variables were analyzed using Pearson's or Spearman's correlation coefficient. Linear regression was performed. Variable distribution normality was verified using the Shapiro-Wilk test. Results The study included 250 patients (110 male, mean age 61.23 ± 14.34) with HT, treated at a hypertension clinic. In the CAT questionnaire individual questions pertaining to satisfaction with physician communication (on the CAT) were rated "excellent" 28.4-50.4% of the time. The best-rated aspects of communication included: letting the patient talk without interruptions (50.4% "excellent" ratings), speaking in a way the patient can understand (47.6%), and paying attention to the patient (47.2%). According to patient reports, physicians most commonly omitted such aspects as encouraging the patient to ask questions (28.4%), involving them in decisions (29.2%), and discussing the next steps (35.2%). The respondents had a low level of adherence to pharmaceutical treatment (16.63 ± 4.6). In terms of self-care, they scored highest in self-care management (64.17 ± 21.18), and lowest in self-care maintenance (56.73 ± 18.57). In correlation analysis, satisfaction with physician-patient communication (total CAT score) was positively correlated with all SCHI domains (self-care maintenance β = 0.276, self-care management β = 0.208, self-care confidence β = 0.286, p < 0.05), and negatively correlated with ARMS scores (indicating better adherence). Conclusions Satisfaction with physician-patient communication has a significant impact on self-care and pharmaceutical adherence in patients with hypertension. The more satisfied the patient is with communication, the better their adherence and self-care. Trial registration SIMPLE: RID.Z501.19.016.